International marketing - Cateora, Philip R. (Homewood, Ill. : Irwin, 1987)
This reflects the pervasiveness of the competition in businesses resulting change in orientation from international marketing to the more encompassing global marketing.
Includes index
Includes bibliographical references
kjo 16/01/2019
Loans
Keywords: Export marketing; International business enterprises